CONTEXTUAL PHILOSOPHY: AN ESSENTIAL PILLAR FOR THE CHURCH’S VISION IN THE FUTURE - Wanjala, Frederick (Asian Horizons, 2015)
For the success of the mission of the Church, constant adaptation of her perennial teachings to the changing global contexts is necessary. Although the Good News of the Kingdom of God consists in permanent gems and is consequently unchangeable from the substantial perspective therefore, the need to couch this divine message into categories of thought relevant to specific peoples is undeniable. This is the content proffered to the Church in general, and to theologians in particular in several magisterial documents such as Ecclesia in Africa and Fides et Ratio of John Paul II on the one hand, and Aeterni Patris of Leo XIII, on the other. Basing itself on the African situation, this article argues that the contemporary mission of evangelization has to be anchored on the cherished values inherent in the cultures of the various peoples. The kernel of Divine Revelation (Scripture and Tradition) has to be maintained intact, but the cultural expressions which serve as the vehicle for imparting this treasured Word have to be interpreted using the positive dimensions found within the numerous world-views of Christ’s flock. Through this way of repackaging the eternal Word, the Church will be able to remain relevant to the modern world which is tending towards an appreciation of transient values at the expense of permanent ones.